2005
DOI: 10.1093/glycob/cwi078
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ganglioside decreases cholesterol content, caveolin expression and inflammatory mediators in rat intestinal microdomains

Abstract: Membrane microdomains rich in cholesterol and sphingolipids, including gangliosides (GGs), are known to be important regions for cell signaling and binding sites for various pathogens. Cholesterol depletion inhibits the cellular entry of pathogens and also reduces inflammatory signals by disrupting microdomain structure. Our previous study showed that dietary gangliosides increased total ganglioside incorporation while decreasing cholesterol in the intestinal mucosa. We hypothesized that diet-induced reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
3
25
0
Order By: Relevance
“…The decreased serum levels of several cytokines in mice fed the experimental diet suggest that MFGM reduces the inflammatory response following stress. Our results are consistent with those investigating the effects of sphingolipids and gangliosides on inflammation (Dalbeth et al 2009;El Alwani et al 2006;Park et al 2007;Park et al 2005), suggesting that the high sphingolipid content of MFGM could be responsible for the lowered inflammatory response. Gut barrier dysfunction has been identified as a result of cytokine induction due to inflammation (Sun et al 1999).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The decreased serum levels of several cytokines in mice fed the experimental diet suggest that MFGM reduces the inflammatory response following stress. Our results are consistent with those investigating the effects of sphingolipids and gangliosides on inflammation (Dalbeth et al 2009;El Alwani et al 2006;Park et al 2007;Park et al 2005), suggesting that the high sphingolipid content of MFGM could be responsible for the lowered inflammatory response. Gut barrier dysfunction has been identified as a result of cytokine induction due to inflammation (Sun et al 1999).…”
Section: Discussionsupporting
confidence: 91%
“…While the mechanism of how gut barrier dysfunction occurs is unclear, pro-inflammatory cytokines, such as, IL-4, IL-13, IFN-, and TNF-α, have been reported to increase the permeability of intestinal epithelia (Fink 2003;Lewis and McKay 2009;Yajima et al 2009). Several studies suggest that various milk sphingolipids, including sphingomyelin and gangliosides, positively affect the gut by exhibiting a protective effect against colon cancer (Dillehay et al 1994;Duan and Nilsson 2009;Nilsson and Duan 2006;Schmelz et al 1996;Schmelz et al 2000), and other studies have linked sphingolipids and other milk fat fractions containing phospholipids and gangliosides to the inhibition of a pro-inflammatory response and gut barrier protection (Dalbeth et al 2009;El Alwani et al 2006;Park et al 2007;Park et al 2005;. One source of a variety of dietary sphingolipids is MFGM.…”
Section: Mfgm and Inflammationmentioning
confidence: 99%
“…Gangliosides detected in this study are glycosphingolipids, which modulate cell signal transduction and act as specific receptors for certain glycoprotein hormones. It has been reported that dietary gangliosides decrease cholesterol content, thus exerting a potential anti-inflammatory effect (Park et al, 2005). Salicornia does not synthesize most of the metabolites under stress conditions (Supplementary Table S3), as synthesis of metabolites are known to be environmentally dependent and energy diverts to the stress responses that are involved in complex regulatory networks, including metabolism adjustment and gene expression (Fraire-Velázquez & Balderas-Hernández, 2013;Krasensky & Jonak, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent data demonstrate that dietary ganglioside reduces cholesterol content, PAF content, and caveolin-1 expression in intestinal lipid microdomains (14). Cholesterol content reduction or caveolae disruption inhibits inflammatory signals into epithelial cells (15,16).…”
Section: Introductionmentioning
confidence: 95%
“…Thus, we hypothesized that dietary gangliosideYinduced decrease in cholesterol content in microdomains will inhibit proinflammatory signals induced by acute systemic LPS treatment in developing rat intestine. Because the hypothesis was based on our previous studies of the small intestine (13,14), the present study was focused on intestinal tissue.…”
Section: Introductionmentioning
confidence: 99%